2012
DOI: 10.4274/jcrpe.811
|View full text |Cite
|
Sign up to set email alerts
|

Different Aspects of Kidney Function in Well-Controlled Congenital Hypothyroidism

Abstract: Objective: Congenital hypothyroidism (CH) increases the prevalence of kidney and urogenital malformations. There are limited studies considering different aspects of kidney function in well-controlled CH patients. We evaluated some features of kidney function in euthyroid children with CH who have been receiving thyroxine hormone since early life.Methods: This cross-sectional study was conducted in Isfahan, Iran, on 74 children aged 2-15 years old (36 CH patients and 38 healthy children). Inclusion criteria fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A study conducted in Greece [ 37 ], reported an association between albuminuria and severe obstructive sleep apnea in children aged 2–14 years, which occurred as a result of hypoxemia (oxidative stress). Congenital hypothyroidism and Kwashiorkor disease have also been studied, although no relationship with albuminuria has been established to the best of our knowledge [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in Greece [ 37 ], reported an association between albuminuria and severe obstructive sleep apnea in children aged 2–14 years, which occurred as a result of hypoxemia (oxidative stress). Congenital hypothyroidism and Kwashiorkor disease have also been studied, although no relationship with albuminuria has been established to the best of our knowledge [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…DNA and protein damage induced by oxidative stress were observed in experimental hypothyroid animals (3,4) . Fortunately, the glomerular filtration rates between patients with CH and healthy children were not significantly different, although Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/30/15 6:58 AM the mean values for fractional excretion of sodium and potassium were significantly higher in patients with CH (5) . CH may increase the prevalence of oxidative stress, but little is known about the effect of well-controlled CH on early renal injury and DNA damage.…”
Section: Introductionmentioning
confidence: 86%
“…In several studies, the association of overt and/or subclinical primary hypothyroidism with GFR reduction and elevated serum creatinine has been demonstrated, in addition to effects on salt and water homeostasis [ 4 , 8 , 12 ]. These effects are generally normalized following levothyroxine therapy in adult hypothyroid patients and can be improved in hypothyroid patients with chronic kidney disease (CKD) [ 4 , 13 , 14 , 15 ]. In addition, it is remarkable that patients with appropriately treated vs. untreated thyroid disorders have a lower risk of developing renal dysfunctions [ 1 , 4 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In light of the importance of an early detection of renal damage in hypothyroidism, a correct therapeutic approach is fundamental to decrease the risk of CKD development [ 13 , 14 , 15 ]. Similarly, a precise and reliable measure of renal function in hypothyroid patients is strongly desirable.…”
Section: Introductionmentioning
confidence: 99%